2000
DOI: 10.1152/physrev.2000.80.1.361
|View full text |Cite
|
Sign up to set email alerts
|

Oxysterols: Modulators of Cholesterol Metabolism and Other Processes

Abstract: Oxygenated derivatives of cholesterol (oxysterols) present a remarkably diverse profile of biological activities, including effects on sphingolipid metabolism, platelet aggregation, apoptosis, and protein prenylation. The most notable oxysterol activities center around the regulation of cholesterol homeostasis, which appears to be controlled in part by a complex series of interactions of oxysterol ligands with various receptors, such as the oxysterol binding protein, the cellular nucleic acid binding protein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
687
2
18

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 873 publications
(737 citation statements)
references
References 1,174 publications
15
687
2
18
Order By: Relevance
“…Hence, it is reasonable to suspect that the in situ formation of 7DHC in a highly oxidizing environment would result in the progressive conversion of at least some of the 7DHC to oxysterols, which would then compromise cellular functions and viability, ultimately resulting in the observed retinal degeneration. It is known that the levels of oxysterol required to induce various pathological sequellae are extremely small, compared to the steady-state levels of the parent sterol (Schroepfer, 2000;Panini and Sinensky, 2001;Chang and Phelan, 2002). Since such oxysterol formation is potentiated by light exposure, one might think that this would explain the observed exacerbation of retinal damage in the SLOS rat model by intense light.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is reasonable to suspect that the in situ formation of 7DHC in a highly oxidizing environment would result in the progressive conversion of at least some of the 7DHC to oxysterols, which would then compromise cellular functions and viability, ultimately resulting in the observed retinal degeneration. It is known that the levels of oxysterol required to induce various pathological sequellae are extremely small, compared to the steady-state levels of the parent sterol (Schroepfer, 2000;Panini and Sinensky, 2001;Chang and Phelan, 2002). Since such oxysterol formation is potentiated by light exposure, one might think that this would explain the observed exacerbation of retinal damage in the SLOS rat model by intense light.…”
Section: Discussionmentioning
confidence: 99%
“…A hallmark of SLOS is the abnormal and excessive accumulation of 7-dehydrocholesterol (7DHC), an immediate precursor of cholesterol (Tint et al, 1994). 7DHC is extremely labile to oxidation (Girotti, 2002), far more so than is cholesterol, and oxysterols are highly toxic to cells (Chang and Phelan, 2002;Panini and Sinensky, 2001;Schroepfer, 2000;Gaoua et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…24,[31][32][33] They may also exert their effects by lowering cholesterol availability for cell membrane formation by inhibiting 3-hydroxy-methylglutaryl coenzyme A reductase (HMG-CoA reductase), a key enzyme in cholesterol synthesis. 34 Cholesterol oxides bind to specific membrane receptors or cytosolic binding proteins, leading to the perturbation of cholesterol synthesis. [35][36][37] It was also shown that 7b-hydroxycholesterol (7b-OHchol) and 7-ketocholesterol may initiate nonapoptotic death in U937 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Cytotoxicity of 7b-OHchol or other cholesterol oxides have been reported on HT-29 and SW620 human colon cancer cells. 39 Since 7b-OHsito and 7b-OHchol are the most abundant hydroxysterols 34,40 present in food after cooking and storage, it was of interest to compare their cytotoxic effects. In order to determine whether both molecules induced the same or different apoptotic process in cancer cells, we assessed cell viability, cell cycle analysis, caspases activities and DNA fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively greater sensitivity of certain malignant, as opposed to normal, cells offers an opportunity to use oxysterols as chemotherapeutic drugs. A few investigators have recognized their potential as therapeutic agents (15)(16)(17)(18).…”
mentioning
confidence: 99%